Formulasi Emulgel yang Mengandung Ekstrak Etanol Daun Binahong (Anredera cordifolia (Ten.) Steenis) dan Uji Aktivitasnya terhadap Propionibacterium acnes secara In Vitro - Yani, Tri Nofi; Anwar, Effionora; Saputri, Fadlina Chany (Jurnal Kefarmasian Indonesia, 2016)
Binahong (Anredera cordifolia (Ten.) Steenis) leaves have been known to have antibacterial activity but the activity against Propionibacterium acnes as one of the bacteria that play a role in acne’s pathogenesis is still unknown. Binahong leaves ethanolic extract containing 1,28% of ursolic acid in this study were tested by in vitro against Propionibacterium acnes giving result minimum bactericidal concentration of 0,05%. Emulgel of binahong leaves ethanolic extract in this study had physical stability for 12 weeks. Inhibition zone of binahong leaves ethanolic extract emulgel is larger than clindamycin phosphate 1,2% against Propionibacterium acnes, which is in formula 1 (extract equivalen with MIC 0,05%) is 19,67±1,25 mm and formula 2 (extract equivalen double MIC 0,05%) is 20,67±0,47 mm, while inhibition zone of clindamycin phosphate 1,2% is 16,3±0,47 mm.